2017
DOI: 10.1039/c7fo00031f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different oligosaccharides at various dosages on the composition of gut microbiota and short-chain fatty acids in mice with constipation

Abstract: The aim of this study was to evaluate the effects of three different kinds of oligosaccharides (a fructo-oligosaccharide (FOS) formulation consisting of 95% FOS (FOS95); a galacto-oligosaccharide (GOS) formulation consisting of 90% GOS (GOS90) and an isomalto-oligosaccharide (IMO) formulation consisting of 90% IMO (IMO90)) at dosages of 0.8, 4 g per d per kg bw and 8 g per d per kg bw on the composition and activity of the microbiota in the gut of mice with constipation induced by loperamide. Oligosaccharides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
83
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 49 publications
12
83
0
3
Order By: Relevance
“…Moreover, in another study, after treating constipated mice with three different types of oligosaccharides, the results showed that all three oligosaccharides increased the proportion of acetic acid and decreased those of propionic and butyric acid in the feces. e increase in the proportion of acetic acid and the decreased concentration of butyric acid in feces should alleviate the symptoms of symptoms constipation [19]. However, the effect of SCFAs on colonic contractility, motility, and transit time remains unclear [20].…”
Section: Yogurt Effects On Short-chain Fatty Acidsmentioning
confidence: 99%
“…Moreover, in another study, after treating constipated mice with three different types of oligosaccharides, the results showed that all three oligosaccharides increased the proportion of acetic acid and decreased those of propionic and butyric acid in the feces. e increase in the proportion of acetic acid and the decreased concentration of butyric acid in feces should alleviate the symptoms of symptoms constipation [19]. However, the effect of SCFAs on colonic contractility, motility, and transit time remains unclear [20].…”
Section: Yogurt Effects On Short-chain Fatty Acidsmentioning
confidence: 99%
“…55 Treatment with prebiotics improved the water content of feces, decreased intestinal transit time, enhanced the concentration of short-chain fatty acids in the feces of mice and altered the composition of the gut microbiota. 56 Further, prebiotics have been linked with reduction in body weight, hypertension and inflammation, and improvements in glucose metabolism and dyslipidaemia. 54 The chemical structure of coffee melanoidins remains largely unknown due to the marked complexity and diversity of structures and the consequent difficulty in the isolation of pure melanoidin fractions.…”
Section: F I G U R E 7 Correlation Between Microbial Community (Pointmentioning
confidence: 99%
“…NĂŁo hĂĄ consenso sobre o tamanho e a composição de uma microbiota intestinal saudĂĄvel, entretanto, sugere-se que uma contagem inferior a 480.000 genes bacterianos esteja relacionada Ă  maior massa corporal de gordura, Ă  resistĂȘncia Ă  insulina, Ă  dislipidemia e Ă  inflamação sistĂȘmica (LE CHATELIER et al, 2013;TURNBAUGH et al, 2009;COTILLARD et al, 2013 LIU et al, 2016;CHEN et al, 2017). Estudos experimentais utilizam doses de frutanos variadas, que podem ser ofertadas na composição da dieta (5 a 25%) ou por gavagem (0,8 a 8 g/kg de peso do animal) associadas com diferentes teores lipĂ­dicos da ingestĂŁo calĂłrica, sendo que os perĂ­odos experimentais vĂŁo de semanas a meses (RESPONDEK et al, 2013;LIU et al, 2016;WANG et al, 2017;CHEN et al, 2017;WEITKUNAT et al, 2017;MATSUMOTO et al, 2017;DREW et al, 2018;MAO et al, 2018). A maioria dos estudos utiliza doses que variam de 5 a 10% de frutanos, que sĂŁo ofertadas em perĂ­odos curtos de tempo, cuja duração fica entre 3 e 8 semanas de experimento (RESPONDEK et al, 2013;LIU et al, 2016;MATSUMOTO et al, 2017;DREW et al, 2018…”
Section: 35unclassified
“…). Dois estudos compararam doses de FOS consideradas altas e baixas, tendo encontrado mais benefĂ­cios com a suplementação das doses mais altas do prebiĂłtico; entretanto, ambos foram experimentos de curto prazo (duas e quatro semanas)(MAO et al, 2018;WANG et al, 2017). Apesar de o estudode Mao et al (2018) verificar mais benefĂ­cios com a oferta de 25% de FOS, essa quantidade nĂŁo seria tolerada se reproduzida em humanos, visto que a dose utilizada em estudos clĂ­nicos varia de 5 a 8 g/dia, sendo que 16 g Ă© o limite de tolerĂąncia(HESS et al, 2011).…”
unclassified
See 1 more Smart Citation